Insulin resistance and incident peripheral artery disease in the Cardiovascular Health Study. - Britton, Kathryn A; Mukamal, Kenneth J; Ix, Joachim H; Siscovick, David S; Newman, Anne B; de Boer, Ian H; Thacker, Evan L; Biggs, Mary L; Gaziano, J Michael; Djoussé, Luc (Vasc Med, 2012)
Type 2 diabetes is a risk factor for peripheral artery disease (PAD), and insulin resistance is a key feature of diabetes and pre-diabetes. No longitudinal epidemiological study has examined the relation between insulin resistance and PAD. Our study analyzed the association of quartiles of the homeostatic model of insulin resistance (HOMA-IR) and the development of PAD defined by two methods. PAD was first defined as the development of an abnormal ankle-brachial index (ABI) (dichotomous outcome) after 6 years of follow-up. PAD was alternatively defined as the development of clinical PAD (time-to-event analysis). The study samples included adults over the age of 65 years who were enrolled in the Cardiovascular Health Study, had fasting measurements of insulin and glucose, had ABI measurements, and were not receiving treatment for diabetes. Multivariable models were adjusted for potential confounders, including age, sex, field center and cohort, body mass index (BMI), smoking status, alcohol use, and exercise intensity. Additional models adjusted for potential mediators, including blood pressure, lipids, kidney function, and prevalent vascular disease. In the ABI analysis (n = 2108), multivariable adjusted models demonstrated a positive relation between HOMA-IR and incident PAD (odds ratio = 1.80 comparing the 4th versus 1st quartile of HOMA-IR, 95% confidence interval [CI] 1.20-2.71). In the clinical PAD analysis (n = 4208), we found a similar relation (hazard ratio = 2.30 comparing the 4th versus 1st quartile of HOMA-IR, 95% CI 1.15-4.58). As expected, further adjustment for potential mediators led to some attenuation of effect estimates. In conclusion, insulin resistance is associated with a higher risk of PAD in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Blood Glucose; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Fasting; Female; Health Surveys; Humans; Incidence; Insulin; Insulin Resistance; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Peripheral Arterial Disease; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Metabolic syndrome and risk of incident peripheral artery disease: the cardiovascular health study. - Garg, Parveen K; Biggs, Mary L; Carnethon, Mercedes; Ix, Joachim H; Criqui, Michael H; Britton, Kathryn A; Djoussé, Luc; Sutton-Tyrrell, Kim; Newman, Anne B; Cushman, Mary; Mukamal, Kenneth J (Hypertension, 2014)
Prior studies evaluating metabolic syndrome (MetS) and incident peripheral artery disease (PAD) have been limited by use of modified MetS criteria and restriction to clinical PAD end points. We investigated MetS and risk of developing a low ankle-brachial index (ABI) and clinical PAD in the Cardiovascular Health Study, a population-based cohort of adults aged ≥65 years. Participants with MetS met at least 3 of 5 Adult Treatment Panel III criteria. Baseline C-reactive protein-MetS or fibrinogen-MetS were defined as presence of 3 of 6 components, with elevated C-reactive protein (>3 mg/L) or fibrinogen (>341 mg/dL) as a sixth component. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among a subset of 1899 individuals with 2 ABI measurements 6 years apart. Over a median follow-up of 13.7 years, 4632 individuals were followed up for clinical PAD, defined as revascularization or diagnosed claudication. Adult Treatment Panel III MetS was associated with both incident low ABI (risk ratio, 1.26; 95% confidence interval [CI], 1.00-1.58) and clinical PAD (hazard ratio, 1.47; 95% CI, 1.11-1.94). Incorporating C-reactive protein or fibrinogen into Adult Treatment Panel III criteria identified an additional 16% to 20% of individuals as having MetS, and both C-reactive protein-MetS and fibrinogen-MetS were associated with incident low ABI (risk ratio, 1.36; 95% CI, 1.07-1.72 and risk ratio, 1.43; 95% CI, 1.13-1.81, respectively) and clinical PAD (hazard ratio, 1.56; 95% CI, 1.17-2.08 and hazard ratio, 1.55; 95% CI, 1.17-2.07, respectively). Among Adult Treatment Panel III MetS criteria, risk of PAD was most strongly associated with hypertension.
Keywords: Aged; Ankle Brachial Index; C-Reactive Protein; Female; Fibrinogen; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Metabolic Syndrome; Peripheral Arterial Disease; Prevalence; Risk Factors; Vasculitis